2015
DOI: 10.1016/j.jnoncrysol.2014.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Nepheline crystallization in boron-rich alumino-silicate glasses as investigated by multi-nuclear NMR, Raman, & Mössbauer spectroscopies

Abstract: A spectroscopic study was conducted on six simulant nuclear waste glasses using multi-nuclear NMR, Raman, and Mössbauer spectroscopies exploring the role of Si, Al, B, Na, and Fe in the glass network with the goal of understanding melt structure precursors to deleterious nepheline crystal formation. NMR showed two sites each for Al, Si, and Na in the samples which crystallized significant amounts of nepheline, and B speciation changed, typically resulting in more B(IV) after crystallization. Raman spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 92 publications
6
51
1
Order By: Relevance
“…Table summarizes the published chemical shift values for crystalline species of interest for this work, including nepheline, carnegieite, eucryptite, and related phases . In general, for framework cations 29 Si and 27 Al, the NMR results for both glasses and crystals indicate primarily Q 4 units, as would be expected for a stoichiometric glass with Al/alkali ~1.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Table summarizes the published chemical shift values for crystalline species of interest for this work, including nepheline, carnegieite, eucryptite, and related phases . In general, for framework cations 29 Si and 27 Al, the NMR results for both glasses and crystals indicate primarily Q 4 units, as would be expected for a stoichiometric glass with Al/alkali ~1.…”
Section: Discussionmentioning
confidence: 91%
“…Crystallization of aluminosilicate phases has previously been shown to be detrimental to the chemical durability of HLW glasses as it extracts more durable components (i.e., alumina and silica) from the glass and enriches the residual glass in less durable components (such as boron and alkali) . The most common phase observed to form upon cooling of glass melts in the compositional space of interest is nepheline (nominally NaAlSiO 4 ), a tectosilicate feldspathoid . Electron probe microanalysis (EPMA) of nepheline dendrites in slow‐cooled HLW glasses revealed that their general formula could be written as (K,Na,Ca,Mg,vac) 2 Hex (Na,Ca,Mg,vac) 6 Oval (Si,Al,Fe) 16 O 32 where “Hex” refers to the large hexagonal rings comprising Fe‐O, Al‐O, or Si‐O tetrahedra, “Oval” refers to the so‐called “squashed” six‐membered rings of the same tetrahedral building blocks, and “vac” refers to a vacancy .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from a number of sources indicates that the Al 3+ will occur predominantly as [4] Al 3+ [27,[33][34][35][36][37][38]. Manganese is readily reduced from Mn 3+ to Mn 2+ in glasses prepared under oxidising [40] also determined that the average coordination of Mn 2+ in radioactive waste borosilicate glasses is approximately 5, therefore it is assumed for our models that Mn is present as 50% [4] Mn 2+ and 50% [6] Mn 2+ , in order to obtain an average of [5] Mn 2+ .…”
Section: +mentioning
confidence: 99%
“…The peaks indicate there exists short range order (and in some cases medium range order) in glasses. Generally, in borosilicate glasses containing high concentration of Al 2 O 3 , there is tendency for the formation of crystalline alumino-silicate phase (like for example the nepheline phase) [15]. However, no sharp peaks characteristic of crystalline phases could be seen in the XRD patterns confirming that no crystalline phase separation has taken place in these samples.…”
mentioning
confidence: 92%